INCREASING THE ROLE OF THE SERVICE SECTOR IN PROVIDING EMPLOYMENT TO THE RURAL POPULATION - Khudayarova Maftuna Shavkatovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2021)
The article considers various classifications of factors affecting the financial potential of the regions, and in terms of the development of production capacity in the example of Surkhandarya region, compared with other regions of the Republic of Uzbekistan. As a result of the study, proposals were developed to increase the financial capacity of the regions and implement an effective strategy of socio-economic development.